EQCM Analysis of the Insertion Phenomena in a n-Doped Poly-Alkyl-Terthiophene With Regioregular Pattern of Substitution - Dini, Danilo; Salatelli, Elisabetta; Decker, Franco (Frontiers in Chemistry, 2021)
In the present work, we have undertaken the study of the n-doping process in poly-3,3″-didodecyl-2,2′:5′,2″-terthiophene (poly-33″-DDTT) employing the electrochemical quartz crystal microbalance (EQCM). The present study aims at understanding how cathodic charge in n-doped poly-33″-DDTT is compensated. For this purpose, the in situ analysis of the variations of the polymeric mass has been considered. Poly-33″-DDTT was obtained as a thin coating onto a metallic substrate via the anodic coupling of the corresponding monomer 3,3″-didodecyl-2,2′:5′,2″-terthiophene (33″-DDTT). When subjected to electrochemical n-doping in the polarization interval -2.5 ≤ Eappl ≤ 0 V vs. Ag/Ag+, the films of poly-33″-DDTT varied their mass according to a mechanism of cations insertion during n-doping and cations extraction during polymer neutralization. In fact, the electrochemical doping of polythiophenes requires the accompanying exchange of charged species to maintain the electroneutrality within the structure of the polymer in all states of polarization. At the end of a full electrochemical cycle (consisting of the n-doping and the successive neutralization of poly-33″-DDTT), the polymer retains a fraction of the mass acquired during n-doping, thus manifesting the phenomena of mass trapping. The combined analysis of electrochemical and microgravimetric data suggests that poly-33″-DDTT in the n-doped state undergoes (or electrocatalyzes) uncontrolled electrochemical reactions that are not accompanied by mass variations.